Effectiveness of In Virtuo Exposure and Response Prevention Treatment Using Cognitive–Behavioral Therapy for Obsessive–Compulsive Disorder: A Study Based on a Single-Case Study Protocol - Laforest, Mylène; Bouchard, Stéphane; Bossé, Jessie; Mesly, Olivier (Frontiers in Psychiatry, 2016)
Obsessive-compulsive disorder (OCD) is characterized by the presence of distressing, recurrent and intrusive thoughts, impulses, or doubts as well as behavioral or mental rituals. OCD has various subtypes, including the fear of contamination in which individuals fear bacteria, germs, disease, or bodily secretions and engage in clinically significant cleaning and avoidance rituals. Cognitive-behavioral therapy is an effective treatment for OCD and involves, among other therapeutic strategies, exposing patients to feared stimuli while preventing them to engage in compulsive behaviors. In recent years, virtual reality has shown the potential of in virtuo exposure with people suffering from anxiety disorders and OCD. The objective of the current pilot study is to examine the effectiveness of a CBT program where exposure in conducted in virtuo. Three adults suffering from OCD with a dominant subtype of contamination were enrolled in a single-case design with multiple baselines across participants. The presence and intensity of obsessions and compulsions were assessed daily during baselines of 3-, 4- or 5-week, and a 12-session treatment. Follow-up information was gathered after four and eight months. Treatment outcome is assessed with visual inspection of the graphs and ARMA time-series analyses. Clinical information, self-reports, and details of the treatment are provided for each patient. Statistical analyses for the time-series data revealed a statistically significant improvement in all three participants, but global improvement is considered positive for only two. This study innovates in proving preliminary support for the usefulness of VR in the CBT of OCD with contamination features.